Health Care Reform and Long-Term Care in the Netherlands - Schut, Erik (OECD Publishing, 2013)
The Netherlands, as other OECD countries, faces the challenge of providing high quality health and long-term care services to an ageing population in a cost-efficient manner. In the health care sector, reforms have aimed at introducing more competition. Despite major changes and some positive effects, the reforms run the risk of getting stuck in the middle between a centralised system of state-controlled supply and prices and a decentralised system based on regulated competition, providing insufficient incentives for provision of quality services and expenditure control. The main challenges are to complete the transition to regulated competition in health care provision, to strengthen the role of health insurers as purchasing agents and to secure cost containment in an increasingly demand-driven health care sector. In 2012, reforms expanded the role of the market in the hospital sector and reinforced budget controls. Both measures are not consistent and may jeopardize both objectives. More competitive markets require, at least, provision of good quality information, appropriate financing and better efficiency incentives. In view of population ageing, current policies mean that the cost of long-term care is set to more than double over the coming decades. Insufficient incentives for cost-efficient purchasing of long-term care should be addressed. However, the government?s plan to transfer long-term care purchasing to health insurers is unpromising unless additional measures ensure that insurers bear the associated financial risks. In addition, home care should be further encouraged at the expense of institutional care, while screening and targeting should be improved. This Working Paper relates to the 2012 OECD Economic Survey of the Netherlands (www.oecd.org/eco/surveys/Netherlands
Keywords: Social Issues/Migration/Health; Economics; Netherlands